Dental implants in an orthodontically created spaces using NiTi open coil spring in anterior and premolar regions - Abduljabbar, Omar Fawzi; Shihab, Omed I.; Omer, Othman A. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Orthodontic space opening is a common treatment for congenitally missing teeth. Dental implants are often used to replace the missing tooth to establish ideal esthetics without restoring the adjacent teeth. This study aimed to investigate the outcome of implants placed in orthodontically created bone. Methods: Fifty dental implants were used for rehabilitation of lost tooth/teeth in 30 patients after space creation using orthodontic treatment. Patients with congenital and traumatic missing tooth/teeth, who lost the space for accommodation of normal size crown, and patients with spacing were enrolled in the study. NiTi open coil spring was used for space creation. The patients were followed up clinically and radiographically (OPG). Results: Out of 50 implants, the success rate was 78% (39 implants). Eleven implants (22%) failed to get osseointegration. Mean age of the patients was 26.33. Female patients constituted 63.33%, and male patients 36.67%. A new one replaced all the failed implants. Most of the failures were in the mandible. Conclusion: Orthodontic treatment can be used as a type of osteodistraction method for provision of an acceptable amount of bone for dental implants. The quality of the gained bone can be improved by offering sufficient time for healing.